Knowledge attitude and practice (KAP) of diabetes in Mathura Uttar Pradesh - An observational study - Jyoti Goyal; Seema Raghav; Navin Kumar; Paramjeet Singh Bhatia; Purnima Bajpai (International Journal of Medical Research and Review, 2019)
Introduction: Objective of this study is to determine the knowledge, attitude and practice regarding type 2 diabetes in diabetics as well as in Non-diabetics and also to determine the knowledge versus practice gap among diabetics. There is almost no study of this kind from Uttar Pradesh region of India.Material and method: A pretested and validated questionnaire were used for assessment of these parameters. This questionnaire was divided in to 3 parts. First part used for assessment of knowledge in all the study subjects and had 8 questions. Second part had five questions based on risk factors and complication of diabetes. Third part was used only for diabetics and again had five questions based on their health care seeking behavior. A total of 412 study subjects (206 diabetics and 206 Non-diabetics) were interviewed and their responses were noted in this questionnaire form.Results: 50% of the diabetics are in the age group category of 41-60 years. > 50% of non-diabetics are in the age group category 21-40 years. Most of the respondents were aware of symptomatology, non-communicability, need of self-monitoring of glucose at home and rapidly increasing incidence of diabetes. Almost 70 % of diabetics were aware about foot care and Very nominal number of diabetics (7.8%) was consuming sweets daily. A disheartening fact revealed that approximately 87% of diabetics do not carry sugar candy or any form of sugar before leaving home to correct any hypoglycemic episode.Conclusion: Knowledge of symptomatology of diabetes and requirement of self-monitoring of blood glucose at home was adequate among most of the study subjects and uniformly distributed among diabetics and Nondiabetics. More than 80% of diabetics were not aware about hypoglycemia symptoms and its treatment. Training of health care providers and large-scale education and awareness campaigns are the need of the hour for this region to further improve the knowledge and to improve self-care practices among all Diabetics.